MAC Protocols for Cyber-Physical Systems - Xia, Feng (Springer, 2015)
This book provides a literature review of various wireless MAC protocols and techniques for achieving real-time and reliable communications in the context of cyber-physical systems (CPS). The evaluation analysis of IEEE 802.15.4 for CPS therein will give insights into configuration and optimization of critical design parameters of MAC protocols. In addition, this book also presents the design and evaluation of an adaptive MAC protocol for medical CPS, which exemplifies how to facilitate real-time and reliable communications in CPS by exploiting IEEE 802.15.4 based MAC protocols. This book will be of interest to researchers, practitioners, and students to better understand the QoS requirements of CPS, especially for healthcare applications.